“ANALISIS PERSEPSI MASYARAKAT MUSLIM TERHADAP PENGGUNAAN ALAT PEMBAYARAN NON TUNAI DI KOTA MEDAN” - Muhammad Radiansyah (Universitas Islam Negeri Sumatera Utara, 2016)
This research was aimed to analyze the perception of Moslem society to use of non-cash payment instruments in Medan. This reaserch used primary data obtained by distributing questionnaires to the people of Medan totaling 100 samples. The approach used is a quantitative approach to process data obtained from questionnaires after previously transformed into a form numerical data (numbers) by Likert scale. Such data processed with assisted by Eviews program.The analysis used is multiple regression.Results of Public Perception Estimates found that R2 ammounted to 0.836 it means a change of independent variables explain the changes in the dependent variable was amounted to 83.6% and 16.4% explained variables outside the model. While the F-test is obtained by 37.52 or to the value of Prob. 0,000 means jointly variables Efficiency, Security, Infrastructure, Environment Promotion and affect the public perception of Muslim against non-cash Payment Instruments in Medan. Efficiency Variable Coefficient research results positive and significant impact on the public perception of Non-Cash Payment Instrument with t-stat of 2.814 is greater than t-table is 1.661. Security has positive influence and significant on the public perception of Non-Cash Payment Instrument with t-stat of 2.437 is greater than t-table is 1.661. Infrastructure has positive influence and significant on the public perception of Non-Cash Payment Instrument with t-stat of 2.815 is greater than t-table is 1.661. Promotion has positive and significant on the public perception of Non-Cash Payment Instrument as it has a t-stat of 2.236 is greater than t-table is 1.661. Environment has positive influence and significant on the public perception of Non-Cash Payment Instrument with t-stat of 2.555 is greater than t-table is 1.661.So that can be concluded of the infrastructure variable most significant effect on the perception of the Muslim community in using non-cash payment instruments in Medan. Bank Indonesia is expected to more aggressively again in the dissemination of non-cash payment and the benefits of using it where a lot of people who do not understand at all about electronic payments.